Human Immunodeficiency Virus–Associated Pulmonary Arterial Hypertension Diagnosed Postpartum. Issue 1 (January 2015) - Newman, Tondra; Cafardi, John M.; Warshak, Carri R.
Abstract : BACKGROUND: Human immunodeficiency virus (HIV) is a significant risk factor for pulmonary arterial hypertension. There is a significant added risk for maternal mortality when superimposed on the physiologic changes of pregnancy. CASE: A 37-year-old HIV-positive woman underwent caesarean delivery at 27 weeks of gestation for chorioamnionitis and malpresentation after premature rupture of membranes. Postpartum, she was diagnosed with HIV-associated pulmonary arterial hypertension, which was managed successfully with sildenafil and ambrisentan. CONCLUSION: Pulmonary arterial hypertension associated with HIV is a life-threatening complication that may occur in pregnant women with HIV. The rarity of the condition, overlapping with symptoms commonly seen in pregnancy, and its broad differential diagnosis may confound the diagnosis. Prompt recognition and therapy are required to optimize clinical outcomes. Abstract : Pulmonary arterial hypertension associated with human immunodeficiency virus is a life-threatening complication that may occur in pregnant women with human immunodeficiency virus.